Assessment of Immunogenicity of Adjuvanted Quadrivalent Inactivated Influenza Vaccine in Healthy People and Patients With Common Variable Immune Deficiency - Kostinova, Aristitsa Mikhailovna; Akhmatova, Nelli Kimovna; Latysheva, Elena Alexandrovna; Dagil, Yulia Alexeevna; Klimova, Svetlana Valentinovna; Vlasenko, Anna Egorovna; Khromova, Ekaterina Alexandrovna; Latysheva, Tatyana Vasilievna; Kostinov, Mikhail Petrovich (Frontiers in Immunology, 2020)
Background. Recent addition to vaccines of adjuvants has been actively used to enhance the immunogenicity. However, the use of adjuvants for the development of quadrivalent inactivated influenza vaccines (QIV) is currently limited. The aim of this study was to examine immunogenicity of adjuvanted QIV in healthy people and patients with primary immune deficiency - common variable immune deficiency (CVID). Methods. In total before the flu season 2018-2019 in the study were involved 32 healthy volunteers aged 18-52 years and 6 patients with a confirmed diagnosis of CVID aged 18-45 years. To evaluate antibody titres 21 days after vaccination against the influenza A and B strains a hemagglutination inhibition assay (HI) was used. Results. In healthy volunteers adjuvanted QIV has proved its immunogenicity to strains A/H1N1, A/H3N2, B/Phuket and B/Colorado in seroprotection (90%, 97%, 86% and 66%, respectively), seroconversion (50%, 60%, 52% and 45%, respectively), GMR (6.2, 5.7, 4.2 and 3.4, respectively). Statistically significant differences in the level of all criteria were revealed between groups of healthy and CVID patients regardless of the virus strain. Most patients with CVID showed an increase in post-vaccination antibody titer without reaching conditionally protective antibody levels. Conclusion. Immunization with single dose of adjuvanted QIV with decreased amount of hemagglutinin protein to all virus strains due to the use of azoximer bromide forms protective immunity in healthy people, but in patients with CVID the search for new vaccination schemes is the subject of further investigations, as well as the effectiveness of boosterization with adjuvant vaccines.